Evaluación técnico financiera del cambio de sistema de levantamiento artificial actual por bombeo electrosumergible en cuatro pozos del campo la Cira Infantas (2018)
The next project is realized in the La Cira Infantas field. Initially, a description was made of the generalities and geology of the field and the Middle Magdalena Valley Basin. The content of the project corresponds to the description of the artificial lifting systems of the La Cira Infantas Field and failures associated with the artificial lifting systems, focusing on mechanical pumping and progressive cavity pumping. A filter was made using the operating company's fault database, choosing the most critical wells with such survey systems. Subsequently, a second filter was carried out using the selection matrix of lifting systems to analyze the wells, followed by an analysis of the wells with the proposed lifting system, electric submersible pumping, choosing the four most critical wells. An analysis was made of each well with its respective survey system to evaluate the operating conditions of each well. Then, an electric submersible pump was designed for each well according to its basic data.